Relationship between gastritis severity, Helicobacter pylori intensity and mast cell density in the antrum and corpus - Fazilet KAYASELÇUK; Ender SERİN and Yüksel GÜMÜRDÜLÜ and Sema BİRCAN and İlhan TUNCER (Turkish Journal of Gastroenterology, 2019)
-